Using social media to increase the communicative competence of future specialists in the field of ecological tourism - Yekimov Sergey; Nepokupna Tetiana; Shukanova Anzhela; Ryabev Anton; Tonkoshkur Maksym (E3S Web of Conferences, 2021)
The article deals with issues related to the formation of communicative competence among graduates of higher educational institutions in the specialty “tourism”. The importance of proficiency in foreign languages for further professional activities for future specialists in the field of eco-tourism is very high, and therefore there is a need to develop more effective methods of learning foreign languages. The use of social networks in teaching a foreign language allows you to make it more flexible and efficient, as well as more convenient for students . Easy learning increases motivation to learn a foreign language.